The battle of Gettysburg, 1863 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic, 2013)
In 1863, child slave Thomas and his sister Birdie journey north and meet up with Union soldiers who have orders to fight at Gettysburg.
Includes bibliographical references.
Booklist, April 2013.
Kirkus Review, January 2013.
Christian Library, November 2014.
4.1
3-6
Keywords: Gettysburg, Battle of, Gettysburg, Pa., 1863 -- Juvenile fiction; Child slaves -- United States -- Fiction; Gettysburg, Battle of, Gettysburg, Pa., 1863 -- Fiction; Slaves -- Fiction; Historical fiction; Gettysburg (Pa.), Battle of, 1863. -- Fiction; Brothers and sisters -- Fiction; United States -- History -- Civil War, 1861-1865 -- Juvenile fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; United States -- History -- 1861-1865, Civil War -- Fiction; Historical fiction